Factors related of the Incidence of Scabies among Students at Hidayatul Falah Islamic Boarding School of Rejang Lebong Regancy - Chairul Tomas; Yusran Fauzi; Fikitri Marya Sari (Universitas Dehasen Bengkulu, 2026)
Scabies is a contagious skin disease caused by Sarcoptes scabiei mite. Scabies causes intense itching, especially at night, rashes, and scratches that can lead to secondary bacterial infections. Sleep disturbances due to itching can reduce quality of life and trigger stress, anxiety, and decreased concentration. People with scabies often experience negative stigma because the disease is related to poor hygiene, even though it can be transmitted through close contact in crowded environments such as homes, schools, or orphanages. The purpose of this study is to analyze the risk factors for scabies at Hidayatul Falah Islamic Boarding School in Rejang Lebong Regency. This study used a cross-sectional design. The sample size was 66 respondents using stratified random sampling. Data were collected using a questionnaire administered to 66 students at Hidayatul Falah Islamic Boarding School in Rejang Lebong Regency and processed using SPSS. The results of the univariate analysis showed that most respondents (60.6%) had poor personal hygiene, most respondents (65.2%) had sufficient knowledge, most respondents (62.1%) lived in densely populated areas, and most respondents (54.5%) had experienced scabies. The bivariate analysis results showed that there was a correlation between personal hygiene and the incidence of scabies (p value = 0.004), a correlation between knowledge and the incidence of scabies (p value = 0.002), and a correlation between housing density and the incidence of scabies (p value = 0.035) at Hidayatul Falah Islamic Boarding School in Rejang Lebong Regency. It is hoped that Islamic Boarding Schools, with the assistance of local health centers, can optimize preventive and promotional programs about factors related to scabies.